AB1207 Increasing quality of JIA treatment: The pediatric rheumatology care and outcomes improvement network (PR-COIN). (23rd January 2014) - Beukelman, T.; Bingham, C.A.; Gottlieb, B.S.; Griffin, N.; Laxer, R.; Marsolo, K.; Passo, M.H.; Lannon, C.; Margolis, P.; DeWitt, E.M.
Abstract : Background: Children with juvenile idiopathic arthritis (JIA) do not receive optimal care. There is wide variation in selection of treatment, adherence with published guidelines, and the use of evidence-based care delivery processes. Improving the quality of care for JIA by decreasing these existing wide variations is essential to improve long term outcomes and to increase the speed with which new discoveries and knowledge reach patients. PR-COIN is a "learning network" that uses data for quality improvement (QI) and research. Learning networks involve collaborations among multidisciplinary teams of clinicians and staff, patients and families, and researchers to improve delivery of care and patient outcomes. Objectives: The mission of PR-COIN is to build a sustainable learning network to improve the outcomes of care for children with JIA and to accelerate adoption of evidence into medical practice. Methods: PR-COIN is organized based on the Breakthrough Series collaborative improvement model developed by the Institute for Healthcare Improvement. Sites participating in PR-COIN establish a clinical improvement team consisting of 3 or more people including a physician champion and nurse. Teams attend face-to-face learning sessions, and receive intensive training and coaching on how to apply proven strategies for chronic disease management to JIA, including self-management support, delivery system design, decision support, and clinical information systems from nationally recognized quality improvement and JIA experts. During action periods between learning sessions, teams use QI tools to help with implementation of and tests of system changes. Teams collect and submit data to a shared registry regarding their performance on several published quality measures (QM). Teams receive feedback and learn from each other through monthly conference calls and reports of site-specific and aggregate data on QM presented as run charts enabling teams to track performance on QM over time. Results: 12 North American sites are enrolled in the network and show considerable variation along several elements, including number of physicians, staffing, medical records systems, information technology capability and geography. A public website pr-coin.org has a members only section for transparent sharing of data reports. A population management tool allows segmentation of patient populations for targeted interventions. Baseline performance on selected QM include 69% of patients receiving uveitis screening per guidelines, 64% of patients on biologics screened for TB annually, and 100% of patient visits document complete joint counts and pain levels. Current work is focused on areas for improvement. Conclusions: By sharing data and aligning practices, PR-COIN focuses on reducing unwanted variations in care, enhancing learning about how to effectively scale up improvement, and providing infrastructure for patient-centered outcomes research, especially with respect to understanding the comparative effectiveness of healthcare interventions. Disclosure of Interest: T. Beukelman Grant/Research support from: Pfizer, Consultant for: Novartis, C. Bingham: None Declared, B. Gottlieb: None Declared, N. Griffin: None Declared, R. Laxer: None Declared, K. Marsolo: None Declared, M. Passo Grant/Research support from: Pfizer, Consultant for: Pfizer, C. Lannon: None Declared, P. Margolis: None Declared, E. DeWitt: None Declared